A rough guide to molecular solid solutions: design, synthesis and characterization of mixed crystals. Issue 44 (20th July 2018) - Lusi, Matteo
Abstract : Recent literature on molecular solid solutions is reviewed and general empirical rules to help synthesize mixed crystals are summarised. Abstract : Crystalline solid solutions are long-known solid phases that enable the fine tuning of a material's structure and properties. Some of them, like metal alloys, have been employed in everyday life for thousands of years. As a result, these phases represent an important part of materials science. On the contrary, solid solutions that involve organic molecules and their compounds have had a slower development. In the past decades though, the number of publications on molecular solid solutions ( i.e. mixed crystals) has increased significantly, and reports on molecular solid solutions have become common in crystal engineering. The studies have produced new information that can help in understanding such phases and show how to obtain materials with improved and tunable properties. Here, practical principles for the design, synthesis and characterization of molecular solid solutions are summarized and discussed from a crystal engineering perspective.